Food security portal - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The drastic rise in food prices over the past couple of years has raised serious concerns about food and nutrition security across the world. While a coordinated response is urgently needed at international and regional levels, the effectiveness of country level response is critical for responding to the crisis. Coherent action is needed to help vulnerable populations cope with the hikes in their food bills, to assist developing-country farmers to swiftly respond to the opportunity posed by the rising demand for their products, and to provide information for evidence based related macro-economic policies. Since the implications of high and volatile food prices have been radically different across countries and population groups, the appropriate policy responses, as well as their scale, prioritization, and sequencing, must be developed and adapted to country-specific needs and conditions. The goal of the International Food Policy Research Institute's “World Food Crisis” project is improved food security for the poor in developing countries in the current food crisis and increased resilience of their food systems against future crises. This project will support the draft June 2008 UN comprehensive framework for action on the global food crisis which focuses on meeting the immediate needs arising from the crisis as well as building resilience and contributing to longer-term global food security. The project will build a global research-based monitoring and capacity-strengthening device for successful identification and implementation of the appropriate policy actions in response to the food crisis. All of these actions come together at the country level, where the ownership and final accountability for implementation rests. As a central component of the project, this open access policy information portal has been established to provide comprehensive and detailed information country-by-country on food policy developments. We note that currently a lot of information is being collected in an un-coordinated fashion by different international and regional organizations. This portal is designed to pool such information in structured ways and check for data quality and relevance. The portal will contain relevant food crisis response information initially on its 20 partner countries (mostly in Sub-Sahara Africa, but also in Asia and Latin America and the Caribbean) and shall be expanded beyond these pre-selected countries in the context of the project. The portal also includes a research-based capacity-strengthening “tool box” that will be developed to guide country responses. Where needed, advice on urgently needed policy actions will also be facilitated.